Modernization of local communities in Algeria - a diagnostic study - Belkacem BOUMAZA; Willy MICBO KUMBO (Journal of North African Economies, 2025)
This research paper aims to diagnose the local electronic administration in Algeria and to stand on the extent of modernization and digitization of the local communities, which is considered the link between the citizen and the government, as the technological revolution has cast a shadow on all aspects of life, which necessitates changing the mechanisms of administrative work, tools for providing public service and the nature of communication with citizens and economic operators. To achieve the goal of the study, the analytical method was used by dissecting the studied phenomenon and linking its variables to draw conclusions. The study concluded that the local administration, despite the efforts made, is still at the beginning of its path towards electronic transformation; its services are still characterized by bureaucracy in light of the fragility of adopting a decentralized system in the management of local regions, which would generalize general management rules over distinct regions socially, culturally, economically, and administratively